STRATEGI IMPLEMENTASI APLIKASI SISTEM KEUANGAN DESA: STUDI KASUS PEMERINTAH DAERAH KABUPATEN NGANJUK - Zaenal Fanani (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2018)
This study aims to explore the strategy of implementing the village financial system application: a case study of the district government of Nganjuk. The formulation of the problem of this study is how is the implementation and assistance of Nganjuk District village financial management? how did the workshop affect the village financial management of Nganjuk Regency? how is the problem of village financial management in Nganjuk Regency (positive and negative aspects)? The research method was carried out a case study at the Nganjuk Regency Community and Village Empowerment Office (PMD). Data obtained from interviews with informants related to village financial management and observation. The results of the study show that the strategy for implementing the village financial system in Nganjuk district government by using this workshop was very effective and efficient. Problems in the village financial management of Nganjuk Regency are divided into 2 things, positive and negative aspects. Positive aspects include the synergy between the sub-district head, the PMD service, the legal bureau and the inspectorate, the ability of village operators to operate the system (SILOKDES), the completeness of village financial management regulations. Negative aspects include non-compliance with the cycle and delays in disbursing funds, capacity and personnel, non-labor-based development and not fully describing the needs of the village, and the transparency of the plans for the use and accountability of the Village Budget